Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Petani Sawit dan strategi peningkatannya di Kecamatan Muara Tembesi Kabupaten Batang Hari - Nurmaidah Sitanggang; Junaidi; Etik Umiyati; Siti Hodijah; Nurhayani (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to analyze the factors affecting the income of oil palm farmers and formulate strategies to improve it in Muara Tembesi District, Batang Hari Regency. The variables examined include land area, capital, labor, and market price. The research applies a field research method with a descriptive quantitative approach. Data were collected through questionnaires distributed to 98 oil palm farmers selected using a random sampling technique. Data analysis was performed using multiple linear regression with SPSS version 27, while a SWOT analysis was used to formulate income improvement strategies. The results indicate that both simultaneously and partially, land area, capital, labor, and market price significantly influence farmers’ income. The coefficient of determination (R²) value of 0.935 shows that 93.5% of the variation in income can be explained by these four variables, while 6.5% is explained by other factors outside the model. The SWOT analysis positions oil palm farming in Quadrant I (aggressive growth strategy), with key strategies including strengthening farmer institutions, improving access to capital, adopting modern cultivation technologies, and encouraging price stabilization policies for fresh fruit bunches (FFB).